10 years of BiTE immunotherapy: an overview with a focus on pancreatic cancer - Paredes-Moscosso, Solange R. (2024)
Various therapeutic strategies have been developed to treat Pancreatic Cancer (PaCa). Unfortunately, most efforts have proved unfruitful, as the poor prognosis observed in this disease has only attained little improvement in the past 40 years. Recently, deeper understanding of the immune system and its interaction with malignant tumors have allowed significant advances in immunotherapy. Consistent with this, some of the most promising approaches are those that involve T-cell redirection to the tumor site, such as bispecific T-cell engagers (BiTEs). These recombinant antibodies bridge cytotoxic T-cells to tumor cells, inducing target cell-dependent polyclonal T-cell activation/proliferation, which in turn results in elimination of bound tumor cells. Blinatumomab, an anti-CD19 BiTE, received FDA approval in 2014 for Precursor B-cell Acute Lymphoblastic Leukemia. In the past decade, it has demonstrated impressive clinical benefit in patients with B-cell leukemias; and other T-cell engagers have been FDA-approved for hematological malignancies and other diseases, yet limited effect has been observed with other BiTEs against solid cancers, including PaCa. Nevertheless, on May 2024, Tarlatamab, an anti-DLL3 BiTE was approved by the FDA for extensive small cell lung cancer, becoming the first BiTE for solid tumors. In this review, the generation of BiTEs, therapeutic features, manufacturing issues as well as the remaining challenges and novel strategies of BiTE therapy in the context of PaCa, including the lessons we can learn from the use of BiTEs on other types of cancer will be explored.